2006
DOI: 10.1111/j.0909-752x.2006.00168.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of anti‐inflammatory activity of Poria cocos in sodium lauryl sulphate‐induced irritant contact dermatitis

Abstract: An anti-inflammatory efficacy of PoCo on the elicitation phase of the ICD induced by repeated SLS test could be observed and quantified by three independent, non-invasive biophysical assessment parameters. This effect can be explained by its influence on pro-inflammatory enzymes, namely phospholipase A2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 20 publications
0
26
0
2
Order By: Relevance
“…Honey mixture appears useful in the control of dermatitis and psoriasis vulgaris (Al-Waili, 2003). The anti-inflammatory activity of Poria cocos in sodium lauryl sulfate-induced irritant contact dermatitis can be explained by phospholipase A2 (Fuchs et al, 2006). Iijima et al reported that Juzen-taiho-to including Poria cocos and Rehmannia glutinosa corrected the Th1/Th2 imbalance and decreased the elevation of IgE levels as well as the dermatitis in NC/Nga mice (Iijima et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Honey mixture appears useful in the control of dermatitis and psoriasis vulgaris (Al-Waili, 2003). The anti-inflammatory activity of Poria cocos in sodium lauryl sulfate-induced irritant contact dermatitis can be explained by phospholipase A2 (Fuchs et al, 2006). Iijima et al reported that Juzen-taiho-to including Poria cocos and Rehmannia glutinosa corrected the Th1/Th2 imbalance and decreased the elevation of IgE levels as well as the dermatitis in NC/Nga mice (Iijima et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, the anti-inflammatory action was strongly attributed to its multiple components. Phytochemically, FBD-CO 2 was mainly composed of (i) essential oil from A. macrocephala, in which atractylenolide I, III and 14-acetoxy-12-senecioyloxytetradeca-2E,8E,10E-trien-4,6-diyn-1-ol, could inhibit lipopolysaccharideinduced TNF-␣ production, or acetic acid-induced vascular permeability (Li et al, 2007a,b), (ii) essential oil from A. sinensis in which butylphthalide was antagonistic to inflammatory response to brain I/R (Xu and Feng, 2000), and (iii) triterpenes from P. cocos, in which pachymic and dehydrotumulosic acids were potent inhibitors of phospholipase A2 and lipoxygenase (Kaminaga et al, 1996;Cuellar et al, 1997;Giner Larza et al, 2000;Fuchs et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, this fungus is widely used in traditional medicine to treat chronic gastritis, acute gastroenteric catarrh, gastric atony, oedema, nephrosis, dizziness, nausea, and emesis [16,17]. Many previous studies have indicated that its extracts and components have a variety of biological activities such as anti-fungal and anti-bacterial [18], antioxidant [19-21], neuroprotective [22], anti-hypertonic [23], anti-inflammatory [17,24-26], anti-angiogenic [27,28], and anti-cancer effects [29,30]. However, the claimed benefits and their action mechanisms are not fully understood.…”
Section: Introductionmentioning
confidence: 99%